2022
DOI: 10.1007/s00198-022-06420-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hip bone mineral density is associated with high levels of calciprotein particles in patients with Fabry disease

Abstract: Calciprotein particles (CPP) are nanoscale mineralo-protein aggregates that help stabilize excess mineral in the circulation. We examined the relationship between CPP and bone mineral density in Fabry disease patients. We found an inverse correlation with total hip and femoral neck density, but none with lumbar spine. Purpose Calciprotein particles (CPP) are colloidal mineral-protein complexes made up primarily of the circulating glycoprotein fetuin-A, calcium, and phosphate. They form in extracellular fluid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…CPP are colloidal mineral-protein complexes that form in extracellular uid and facilitate the stabilization, transport, and clearance of excess minerals from the circulation. CPP exist in primary (CPP-I) and secondary (CPP-II) form, both of which are reported to be raised in pathological states [17]. One study that looked at mouse models of FD with impaired functioning of the medullary thick ascending limb of the nephron, observed that a decrease in plasma calcium induced an increase in PTH, leading to secondary hyperparathyroidism, which resulted in accelerated bone resorption [18].…”
Section: Calcium and Bone Healthmentioning
confidence: 99%
“…CPP are colloidal mineral-protein complexes that form in extracellular uid and facilitate the stabilization, transport, and clearance of excess minerals from the circulation. CPP exist in primary (CPP-I) and secondary (CPP-II) form, both of which are reported to be raised in pathological states [17]. One study that looked at mouse models of FD with impaired functioning of the medullary thick ascending limb of the nephron, observed that a decrease in plasma calcium induced an increase in PTH, leading to secondary hyperparathyroidism, which resulted in accelerated bone resorption [18].…”
Section: Calcium and Bone Healthmentioning
confidence: 99%